Exposure of workers to pesticide residues during re-entry activities: A review. Issue 8 (17th November 2019) - Toumi, Khaoula; Joly, Laure; Vleminckx, Christiane; Schiffers, Bruno
Abstract: Workers may be exposed to pesticide residues when they enter an area that has been previously treated in order to realize different tasks (e.g., for pruning, cutting, picking, harvesting, pest scouting) or to handle a contaminated crop commodity (e.g., sorting, bundling, packing). A review of the scientific literature on workers exposed to pesticide residues during re-entry tasks provides a comprehensive view of possible exposure routes and a better understanding of the risk assessment context, threshold values, and calculation methodology. Methods assessing the risk to workers health are also reported and discussed. The impact of re-entry activities on health and factors affecting workers exposure are examined. Finally, solutions and mitigation measures aiming to reduce their exposure to pesticide residues are recommended.